Analisis Insiden Computer Vision Syndrome dengan Karakteristik Individu dan Lama Penggunaan Komputer pada Mahasiswa Tingkat Akhir FKP UNRI Dimasa COVID-19 - Atika, Yayang; Darwin Karim; Yulia Irvani Dewi (Indonesian Journal of Nursing Research (IJNR), 2023)
Final year students interact more often in front of computers/laptops for a long time and are vulnerable to eye health, especially during Covid-19. The use of computers/laptops for a long time is one of the risk factors that can cause CVS symptoms. Computer Vision Syndrome (CVS) is a combination of eye and vision problems associated with using a computer or laptop. the study was to describe the incidence of Computer Vision Syndrome with individual characteristics and duration of computer use in final year students of the Faculty of Nursing, the University of Riau during the Covid-19 period. The research design used quantitative descriptive analysis. A sample of 209 final-year students at the faculty of Nursing of Riau University used a total sampling technique. The measuring instrument used is a questionnaire. The age of most respondents was early adulthood (96.0%), the majority were female (90.0%), and the most used computer/laptop screen size was 14 inches (59.3%), with a visibility of 30 cm (48.8 %), and the majority of students do not use assistive devices. The description of final year students who rest their eyes after using a computer/laptop for more than 2 hours is (51.2%), the length of resting the eyes is more than 15 minutes (69.4%), and the most common complaint of CVS symptoms is eye fatigue. (80.9%), and persistent complaints (23.9%). The majority of final year students used computers/laptops within 2 to 4 hours/day and students with complaints of CVS symptoms with severe categories at most thus students are expected to be able to use computers/laptops properly and correctly to avoid CVS symptoms.   Abstrak Mahasiswa tingkat akhir lebih sering berinteraksi didepan komputer/laptop dengan waktu yang lama dan rentan terhadap kesehatan mata, apalagi di masa Covid-19 seperti ini. Penggunaan komputer/laptop yang terlalu lama merupakan salah satu faktor risiko yang dapat menimbulkan gejala CVS. Computer Vision Syndrome (CVS) merupakan gabungan masalah mata dan penglihatan yang berkaitan dengan penggunaan komputer atau laptop. Penelitian bertujuan untuk mengetahui gambaran insiden Computer Vision Syndrome dengan karakteristik individu dan lama penggunaan komputer pada mahasiswa tingkat akhir Fakultas Keperawatan Universitas Riau dimasa Covid-19. Desain penelitian menggunakan analisis deskriptif kuantitatif. Sampel sebanyak 209 mahasiswa tingkat akhir di FKp UNRI yang diambil dengan menggunakan teknik total sampling. Alat ukur yang digunakan adalah kuesioner. Umur responden terbanyak adalah dewasa awal (96,0%), mayoritas jenis kelamin perempuan (90.0%), ukuran layar komputer/laptop terbanyak digunakan adalah 14 inchi (59,3%), dengan jarak penglihatan 30 cm (48,8%), dan mayoritas mahasiswa tidak memakai alat bantu. Gambaran mahasiswa tingkat akhir yang mengistirahatkan mata setelah menggunakan komputer/laptop selama lebih dari 2 jam yaitu (51,2%), lama mengistirahatkan mata lebih dari 15 menit yaitu (69,4%), keluhan gejala CVS yang paling banyak dirasakan yaitu mata lelah (80,9%), dan keluhan yang menetap sebanyak (23,9%). Mayoritas mahasiswa tingkat akhir menggunakan komputer/laptop dalam waktu 2-4 jam/sehari dan mahasiswa dengan keluhan gejala CVS dengan kategori berat adalah yang paling banyak dirasakan sehingga diharapkan mahasiswa dapat menggunakan komputer/laptop dengan baik dan benar agar terhindar dari gejala CVS.